2019
DOI: 10.1002/slct.201901403
|View full text |Cite
|
Sign up to set email alerts
|

Amberlyst‐15‐catalyzed Procedure for the Synthesis of Novel 2,4‐Dihydroxybenzoyl‐1,2,3‐triazoles and Molecular Modelling Studies for Hsp‐90 Inhibition

Abstract: Novel 4‐and 5‐(2,4‐dihydroxybenzoyl) triazoles were prepared from o‐alkynoylresorcinols with by the cycloaddition reaction performed with metal free one step protocol using Bronsted acid Amberlyst‐15 as catalyst for the first time. This procedure enables the synthesis of triazoles bearing o,p‐dihydroxybenzoyl group without the need to protection of hydroxyl groups. Products were obtained in good to excellent yields and with the moderate regioisomeric ratios. In addition, Hsp90 inhibition activities of synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The first loss within 224-327 °C may be caused by decomposition and elimination of the -SO 3 Na groups and the introduced small organic species in the materials [22], while the second loss at higher temperature of 327-448 °C may be attributed to decomposition of the support skeleton [23]. The thermal stability of referential Resin-Cu catalyst was also investigated by TG analysis (Supporting Informa-tion File 1, Figure S3), showing a high thermal stability as well [24][25][26]. The above results indicated that all prepared materials could remain stable in the system when used to catalyze organic reactions.…”
Section: Characterization Of the Prepared Materialsmentioning
confidence: 99%
“…The first loss within 224-327 °C may be caused by decomposition and elimination of the -SO 3 Na groups and the introduced small organic species in the materials [22], while the second loss at higher temperature of 327-448 °C may be attributed to decomposition of the support skeleton [23]. The thermal stability of referential Resin-Cu catalyst was also investigated by TG analysis (Supporting Informa-tion File 1, Figure S3), showing a high thermal stability as well [24][25][26]. The above results indicated that all prepared materials could remain stable in the system when used to catalyze organic reactions.…”
Section: Characterization Of the Prepared Materialsmentioning
confidence: 99%